O conhecimento matemático mobilizado por uma professora em videoaulas sobre função e função afim: uma análise a partir do MTSK - Costa, Vanessa Juliana da (2021)
This research aims to identify and analyze the Specialized know ledge mobilized and made explicit by a mathematics teacher in video lessons for high school students associated with the implementation of "Aula Paraná", a distance learning system developed by the State Education System of Paraná during the COVID-19 pandemic. The analyses developed were qualitative in nature and focused on the content of eight video lessons about the topics "Function" and "Affine Function" and were carried out using the theoretical-analytical model Mathematics Teacher's Specialized Knowledge (MTSK), which focused on the approach of the domain and sub-domains that make up the Mathematical Knowledge - MK. The analyses showed that the knowledge mobilized by the teacher during the video lessons is mostly associated with the sub-domain of KoT, so that the teacher explicitly mentioned knowledge about procedures, definitions, properties and their foundations; representation registers and applications and phenomenology linked to the function theme. Thus, there was little identification of the presence of knowledge associated with the sub-domains that discuss typical elements of mathematics teachers' practice and of mathematical connections.